Multidimensionality of autonomy in universities and higher education (September 14-15, 2018, University of Szczecin) - Murawska, Anna (Filosofiya osvity. Philosophy of Education, 2018)
The article presents central issues discussed during international conference «Crises of autonomy in universities and higher education». The conference was carried out at University of Szczecin, Poland (14-15th September 2018), which has a 25 years long tradition in organizing conferences on higher education. Researchers from Poland, Italy, Lithuania, Ukraine and Great Britain participated in the debate what enabled to show the problems from global perspective. The author mainly refers to the essence of academic autonomy along with its specific features as they were formulated by conference participants. She pointed out dynamics and multidimensionality. Autonomy is not unequivocally positive phenomenon what was time and again underlined at the conference, therefore it release various challenges and threats. The author presents them together with prospects of overcoming them, among them reflexivity oriented education as well as studying and researching based on three pillars: care, curiosity and community.